(untitled) (Research, Society and Development, 2021)
The present work aims to contribute to professionals in the field of Dentistry, information on the identification and notification of sexual abuse in the dental environment, through behavioral analysis and orofacial manifestations. This study consists of a literature review, qualitative of the integrative type. Through queries in the databases: Academic Google, SciELO, BVS, and PubMed, articles were searched between the years 1990 to 2021, preferably with the keywords: Child Sexual Abuse, Compulsory Notification of Abuse, and Sexually Transmitted Infection. Child sexual abuse is often not diagnosed or notified, and the dentist is obliged to notify suspicious situations or confirmation of abuse, in accordance with the Statute of Children and Adolescents - ECA. However, there is little knowledge about child violence, difficulty in identifying the main signs/manifestations of sexual abuse and doubts about how to proceed in these cases, requiring professional guidance to the dental surgeon to help with both diagnosis and registration of child violence. The dental community is essential in the diagnosis/prevention of maltreatment, in the treatment of orofacial injuries resulting from abuse and assistance in reporting child violence, and must be made aware of the fight against child abuse and neglect, taking into account that it can legally respond to failure to carry out the deliberations of the ECA. It is concluded that injuries resulting from mistreatment, including sexual abuse, compromise the orofacial region, and it is essential that dentists are able to identify and report cases of suspected sexual abuse of a vulnerable person.